On the connections between Skyrme and Yang Mills theories - Guillén, Joaquín Sánchez; Ferreira, L. A. [UNESP] (My University, 2002)
Skyrme theories on S3 and S2, are analyzed using the generalized zero curvature. In the first case, new symmetries and integrable sectors, including the | B |= 1 skyrmions, are unraveled. In S2 the relation to QCD suggested by Faddeev is discussed.